2009
DOI: 10.1088/1674-0068/22/06/627-634
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation on Stability of Insulin on Graphene

Abstract: The adsorption dynamics of a model protein (the human insulin) onto graphene surfaces with different sizes was investigated by molecular dynamics simulations. During the adsorption, it has different effect on the stability of the model protein in the fixed and non-fixed graphene systems. The tertiary structure of the protein was destroyed or partially destroyed, and graphene surfaces shows the selective protection for some α-helices in non-fixed systems but not in fixed systems by reason of the flexibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…High contact stabilities were found for both the aromatic tyrosine (Tyr63) and phenylalanine (Phe67) residues with all nanomaterials. The stable π-stacking arrangements between the aromatic rings of the peptide and the electron-rich carbon rings of the surface, suggest that these are the key residues that contribute to the strong interactions between the peptide and the carbonaceous nanomaterials, in line with other studies [23] , [30] [32] , [52] , [77] , [78] .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…High contact stabilities were found for both the aromatic tyrosine (Tyr63) and phenylalanine (Phe67) residues with all nanomaterials. The stable π-stacking arrangements between the aromatic rings of the peptide and the electron-rich carbon rings of the surface, suggest that these are the key residues that contribute to the strong interactions between the peptide and the carbonaceous nanomaterials, in line with other studies [23] , [30] [32] , [52] , [77] , [78] .…”
Section: Resultssupporting
confidence: 86%
“…This feature was determined as fibril-favoring in our previous works on apoC-II(60-70) oligomers [34] , [37] . Other studies have also shown that carbon nanotubes and graphene surfaces facilitate a change in the conformation of peptides [30] , [77] and π-stacking is an efficient mode of biological recognition of π-electron-rich carbon nanoparticles [23] , [30] [32] , [52] , [77] , [78] .…”
Section: Resultsmentioning
confidence: 97%
“…Molecular dynamics simulation predicted that human insulin can be adsorbed onto graphene surfaces and that some proteins would be destroyed or partially destroyed. 142 Water-soluble graphene oxide nanosheets (GO) are oxidation products of graphene nanosheets. GOs have a stronger serum protein adsorption capability than SWNT or MWNT.…”
Section: Nanoparticle-biomolecule Interactionsmentioning
confidence: 99%
“…GBM-hormone interactions. In addition to serum proteins, graphene substrates have also shown strong propensity to interact with hormones present in serum 36,37 . A molecular simulation study demonstrated how insulin hormones present in serum can interact with graphene ribbon-like surfaces of different sizes 36 .…”
Section: Gbm-biomolecular Interactionsmentioning
confidence: 99%